Fishing biology of lumptail searobin, Prionotus stephanophrys (Lockington, 1880) from the multi-purpose fishing fleet during 2017 and 2018 in Ecuador: Acuicultura y Pesca - España-Mindiolaza, Sara (2024)
The  lumptail  searobin  (Prionotus  stephanophrys  Lockington  1881)  is  one  of  the  most captured species as part of the bycatch in hake fishing operations; therefore, this research analyzed the size-weight relationship, gonadosomatic index, and size at sexual maturity of 622 individuals incidentally captured by the polyvalent fishing fleet between 2017 and 2018 in the Ecuadorian coast, where it was observed that the most frequent lengths were 27-28 cm TL for both sexes, with an average length for females of 27.73 ± 2.88 cm LT and for males of 26.78 ± 2.51 cm LT; however, in general, no significant differences were found in size structure in combined years (P>0.05). Additionally,  the  estimated  size  at  sexual  maturity  was  20.22  cm;  therefore,  it  is considered that all incidentally captured individuals are above sexual maturity, with only 3.86% below it. The total length-total weight relationship showed for the species a negative allometric growth; meanwhile, the gonadosomatic index established that the reproductive season corresponds from march to november, and from april to may is  resting  season.  The  highest  incidental  capture  of  individuals,  especially  females,  coincided with the peak of reproductive intensity, with a sex ratio F:M of 1.5:1.